2019
DOI: 10.1186/s12879-019-4425-1
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory pilot study evaluating the supplementation of standard antibiotic therapy with probiotic lactobacilli in south African women with bacterial vaginosis

Abstract: Background To reduce acquisition and relapse of bacterial vaginosis (BV), lactobacilli must be maintained in the vaginal microbiome. Probiotic lactobacilli may aid this purpose. We investigated whether vaginal probiotics (containing Lactobacillus rhamnosus DSM 14870 and Lactobacillus gasseri DSM 14869) would result in vaginal colonisation with lactobacilli in women with and without BV. Methods This prospective, partially randomised, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
(61 reference statements)
0
19
0
4
Order By: Relevance
“…Previous studies have already shown the potential of lactobacilli for delivery of microbicides against HIV-1/SHIV infection including antibody fragments [ 41 , 75 ], the chemokine RANTES [ 76 ], cyanovirin [ 77 ] and two-domain CD4 [ 36 ] in vitro and in animal models. Here we chose L. rhamnosus DSM 14870 as vector, because this strain is already a constituent of EcoVag ® vaginal capsules for treatment of bacterial vaginosis and has been shown to colonize the human vagina [ 45 , 47 , 48 ]. Furthermore, the genome of this strain has been completely sequenced and does not contain antibiotic resistance genes ensuring its safety for clinical applications [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have already shown the potential of lactobacilli for delivery of microbicides against HIV-1/SHIV infection including antibody fragments [ 41 , 75 ], the chemokine RANTES [ 76 ], cyanovirin [ 77 ] and two-domain CD4 [ 36 ] in vitro and in animal models. Here we chose L. rhamnosus DSM 14870 as vector, because this strain is already a constituent of EcoVag ® vaginal capsules for treatment of bacterial vaginosis and has been shown to colonize the human vagina [ 45 , 47 , 48 ]. Furthermore, the genome of this strain has been completely sequenced and does not contain antibiotic resistance genes ensuring its safety for clinical applications [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such preventive products are inexpensive to produce, stable at higher temperatures and easy to applicate at home and thus very promising for developing countries. Further, we have previously shown that L. rhamnosus DSM 14870 could transiently colonize the vagina of women and that weekly administration could increase the persistence of the bacteria on mucosal surfaces [ 47 , 48 ]. It is thus likely that vaginal capsules containing the recombinant lactobacilli would need to be administered on a regular basis to maintain their population level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the microbial composition of the lower female genital tract (FGT) in health and dysbiosis may be geo-adapted, with regional differences in diet, vaginal insertion, hygiene practices and host genetics possibly shaping these [ 19 21 ], it is critical to conduct trials in South Africa to test the effectiveness of probiotics for vaginal health in a local context. While randomized controlled trials (RCTs) assessing the effects of probiotics on BV management have been performed in several other African countries [ 22 , 23 ], only one exploratory pilot study has recently been performed in South Africa, although with a European product that is not locally available [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is clinical equipoise as to whether adjunctive probiotics improve BV cure and/or recurrence rates, as a recent meta-analysis (15) concluded that adjunctive probiotics may improve BV cure rates but that there is currently not enough high-quality clinical evidence to support this approach as superior to antibiotic treatment alone. While randomized controlled trials (RCTs) assessing the effects of probiotics on BV management have been performed in several African countries (16,17), only one exploratory pilot study has recently been performed in South Africa (18). As the microbial composition of the lower female genital tract (FGT) in health and dysbiosis may be influenced by regional factors, including diet, vaginal insertion, hygiene practices and possibly host genetics (19)(20)(21), it is important to conduct such trials in South African women to evaluate the effectiveness of probiotics for vaginal health in a local context.…”
Section: Introductionmentioning
confidence: 99%